1987
DOI: 10.1016/s0007-0785(87)80004-2
|View full text |Cite
|
Sign up to set email alerts
|

Pertussin 30—Preventive for whooping cough?

Abstract: The primary purpose of this study was to be a pilot for a further, larger study to determine whether the homœopathic preparation Pertussin 30c was effective in preventing whooping cough. It was recognized that neither the numbers involved, nor the method followed would of themselves be sufficient to prove efficacy, but it was hoped that a positive result would permit the conclusion to be drawn that a further study would be in the public interest.694 valid replies from 1100 questionnaires sent to the parents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…There is no evidence that homoeopathy can prevent a child from becoming infected with a disease that is preventable by vaccination or that it can reduce the severity of a disease. The Faculty of Homoeopathy acknowledges this33 and recommends the use of conventional vaccines 34. Hahnemann, the founder of homoeopathy, was a supporter of smallpox vaccination 35…”
Section: Alternatives To Vaccinationmentioning
confidence: 99%
“…There is no evidence that homoeopathy can prevent a child from becoming infected with a disease that is preventable by vaccination or that it can reduce the severity of a disease. The Faculty of Homoeopathy acknowledges this33 and recommends the use of conventional vaccines 34. Hahnemann, the founder of homoeopathy, was a supporter of smallpox vaccination 35…”
Section: Alternatives To Vaccinationmentioning
confidence: 99%
“…Both studies suggested for large sample trials. [21,22] During epidemic in France from 1984-1987, Oscillococcinum 200C taken twice daily for 5 days significantly increased the rate of cure within two days (n=478, 237 treated by medicine and 241 on placebo), absence of symptoms at 48 hours, relative risk estimate significantly favours homeopathy (p=0.048), no pain and no fever (p=0.048), recovery rate (headache, stiffness, articular pain, shivering reduction) at 48 hours better in homeopathy group (p=0.032). [23] A randomised double-blind prospective study of thirty participants compared standard vaccination to Influenzinum homoeopathic medicine for 13 weeks.…”
Section: Nosodesmentioning
confidence: 99%